Advances in developing metabolically engineered microbial platforms to produce fourth-generation biofuels and high-value biochemicals. (October 2021) - Aamer Mehmood, Muhammad; Shahid, Ayesha; Malik, Sana; Wang, Ning; Rizwan Javed, Muhammad; Nabeel Haider, Muhammad; Verma, Pradeep; Umer Farooq Ashraf, Muhammad; Habib, Nida; Syafiuddin, Achmad; Boopathy, Raj
Graphical abstract: Highlights: Advances in metabolic engineering offer remarkable opportunities in strain development. Bioengineered microbial platforms offer advantages of higher yields. Engineered strains can produce fourth-generation biofuels and biochemicals. However, efficient product recovery needs future research. Abstract: Producing bio-based chemicals is imperative to establish an eco-friendly circular bioeconomy. However, the compromised titer of these biochemicals hampers their commercial implementation. Advances in genetic engineering tools have enabled researchers to develop robust strains producing desired titers of the next-generation biofuels and biochemicals. The native and non-native pathways have been extensively engineered in various host strains via pathway reconstruction and metabolic flux redirection of lipid metabolism and central carbon metabolism to produce myriad biomolecules including alcohols, isoprenoids, hydrocarbons, fatty-acids, and their derivatives. This review has briefly covered the research efforts made during the previous decade to produce advanced biofuels and biochemicals through engineered microbial platforms along with the engineering approaches employed. The efficiency of the various techniques along with their shortcomings is also covered to provide a comprehensive overview of the progress and future directions to achieve higher titer of fourth-generation biofuels and biochemicals while keeping environmental sustainability intact.